Comparison of osseointegration of Ti–Al6V4 and Ti–Al6Nb7 implants: An experimental study - Bozoglan, Alihan; Dundar, Serkan (Elsevier B.V., 2021)
Objective: In this study we aimed to investigate bone–implant connections (BICs) with Ti–Al6V4 and Ti–Al6Nb7 alloys. Two types of surface morphology, resorbable blast material (RBM) and sandblasted and acid-etched surfaces (SLA), were used for implants. Materials and methods: Thirty female Sprague Dawley rats aged 0.5–1 year were used. The rats were randomly separated into three groups: 1) Ti–Al6V4 RBM surface (n = 10), 2), Ti–Al6Nb7 RBM surface (n = 10), and 3) Ti–Al6Nb7 SLA (n = 10) surface implants were surgically integrated in femoral bones. The average roughness (Ra) values for these implants were 1–2 Ra. The rats were sacrificed four weeks after the surgical procedure. For each section, the BIC ratio (%) was determined as a percentage of the total implant surface that was in direct contact with the bone. Results: The BIC ratio was found to be higher in the Ti–Al6Nb7 RBM and Ti–Al6Nb7 SLA groups than in the Ti–Al6V4 RBM group (p < 0.05). There was no statistically significant difference in the BIC ratios between the Ti–Al6Nb7 RBM and Ti–Al6Nb7 SLA groups (p > 0.05). Conclusion: Ti–Al6Nb7 exhibited good biocompatibility with bone cells. Ti–Al6Nb7 alloy could be a candidate material for dental implant production. © 2021
Keywords: Resorbable blast material; Sandblasted and acid etched; Ti-Al6-Nb7; Ti–Al6–V4